2008
DOI: 10.1111/j.1748-1090.2008.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

The principles of rapid response for amphibian conservation, using the programmes in Panama as an example

Abstract: As a direct response to many threats facing seriously threatened amphibian species, including habitat loss, pollution and, more recently, emerging infectious disease, ex situ captive-breeding programmes have proven valuable tools in species preservation. Uniting scientific research and conservation initiatives, here the growth of ex situ conservation for nearly a decade in central Panama is discussed. Looking at three specific projects, it can be demonstrated that collaborative efforts and multipleresponse met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
76
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 7 publications
1
76
0
Order By: Relevance
“…Amphibian declines associated with Bd were well documented at three sites where amphibian diversity (richness and abundance) remains low: Fortuna, Omar Torrijos, and El Valle (Lips, 1999;Lips et al, 2006;Gagliardo et al, 2008). Our sampling revealed that Bd persists at Fortuna 11 years after disease emergence, and is now enzootic at these sites (Table 1).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Amphibian declines associated with Bd were well documented at three sites where amphibian diversity (richness and abundance) remains low: Fortuna, Omar Torrijos, and El Valle (Lips, 1999;Lips et al, 2006;Gagliardo et al, 2008). Our sampling revealed that Bd persists at Fortuna 11 years after disease emergence, and is now enzootic at these sites (Table 1).…”
mentioning
confidence: 88%
“…Captive breeding programs such as at the El Valle Amphibian Conservation Center in Panama and at zoos associated with the amphibian ark project (http:// www.amphibianark.org, March 5, 2008) have already been successful at preserving some species in captivity (Gagliardo et al, 2008). However, repatriation is complicated by enzootic Bd at all sites with a history of disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bd causes the disease chytridiomycosis and is responsible for hundreds of amphibian declines and extinctions, including extirpation of the emblematic Panamanian golden frog, Atelopus zeteki [14,15]. This species was historically present in central-western PanamĂĄ until Bd arrived.…”
Section: Introductionmentioning
confidence: 99%
“…The latter two options have been used successfully as a last resort to prevent extinctions (Mendelson et al 2006, Gagliardo et al 2008. These intensive options are essential for critically endangered species and are currently underway for some Australian frog species at various scales.…”
Section: Introductionmentioning
confidence: 99%